Identifikasi Wisata Kuliner Pedagang Kaki Lima di Kota Makassar - Frizka Kurnia Dedullah; Bambang Heryanto; Isfa Sastrawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2015)
Makassar Old Town area is a community recreation area which generally aims to enjoy the natural beauty of the beach and culinary tourism. Behind the potential of the old city area that offers a variety of tourism and culinary, there are some problems that arise, namely the lack of government attention to culinary tourism, especially for street vendors (PKL). The purpose of this study is to identify the characteristics of culinary tourism, the potential of culinary tourism and the pattern of the spread of culinary tourism locations in the Old City area of ​​Makassar. This research method uses a qualitative descriptive approach through descriptive and spatial analysis using data derived from primary data through direct observation to the field and interviews and secondary data obtained from relevant agencies. The results of this study indicate that the characteristics of culinary tourism based on the type of culinary, namely, the culinary specialties of Makassar are more chosen by the visitors compared to the culinary specialties of Indonesia. Potential culinary tourism in the old city of Makassar is Makassar culinary and seafood for Indonesian culinary. The pattern of the spread of culinary tourism locations is influenced by the presence of tourist objects in the area, Losari Beach Pier, Fort Rotterdam and shopping tourism along the Somba Opu Street corridor.